2016
DOI: 10.3389/fmicb.2016.00212
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering of Vineyard Yeasts: Survival of Interacting Yeast Communities in Grapes Mummified on Vines

Abstract: The conversion of grape must into wine involves the development and succession of yeast populations differing in species composition. The initial population is formed by vineyard strains which are washed into the must from the crushed grapes and then completed with yeasts coming from the cellar environment. As the origin and natural habitat of the vineyard yeasts are not fully understood, this study addresses the possibility, that grape yeasts can be preserved in berries left behind on vines at harvest until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 94 publications
3
59
0
2
Order By: Relevance
“…In the case of the sequenced non-Saccharomyces yeast strains, Z. bailii did not grow on maltose, which is usually assimilated by Z. rouxii and R. mucilaginosa isolates grew on maltose, sucrose, lactose, which are not assimilated by R. minuta. These results are in accordance with those published in [14,21]. Thus, by applying the biochemical tests, we have ensured that these yeast strains have been satisfactorily identified (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…In the case of the sequenced non-Saccharomyces yeast strains, Z. bailii did not grow on maltose, which is usually assimilated by Z. rouxii and R. mucilaginosa isolates grew on maltose, sucrose, lactose, which are not assimilated by R. minuta. These results are in accordance with those published in [14,21]. Thus, by applying the biochemical tests, we have ensured that these yeast strains have been satisfactorily identified (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…The authors observed ethanol to be an efficient inhibitor against fungal species as well, and most of their isolates were ascomycetes. Others have reported similar findings: While exploring the diversity of yeasts in wintering grapes, Sipiczki () noticed that high ethanol concentrations (>8% alcohol by volume (ABV); 4‐week incubation) with raffinose as carbon source effectively decreased the number of yeasts belonging to the Basidiomycota (from 69% of samples to 4%). From 270 mummified berries, he managed to isolate 23 different ascomycete and 13 different basidiomycete yeast species.…”
Section: Isolation and Brewing Potential Of Non‐saccharomyces Sppmentioning
confidence: 70%
“…Indeed, hibernating wasps are one of the only known locations to reliably find these yeasts in the winter when sugar sources are nonexistent, and environments are hostile to cell growth. Yeasts can overwinter in some flowers and mummified fruits [82], but particularly in temperate regions this is likely to be the rare exception. Several species of nectar yeasts have been found to be abundant on bees [31] and in bee nests [37,83], and we speculate that beehives, like wasp foundresses, are important sites for the overwintering of yeasts.…”
Section: Dispersal Of Yeastsmentioning
confidence: 99%